Perfil de resistência a antimicrobianos de Staphylococcus aureus isolados de granjas e frigoríficos de suínos - Masson, Guido Carlos Iselda Hermans [UNESP]; Ferreira, Guadalupe Sampaio [UNESP]; de Oliveira e Silva Carvalho, Luiz Fernando [UNESP] (My University, 2012)
Staphylococcus aureus are involved in a wide range of clinical problems to swine industry as son in humans. Epidemiological researchs prove his potential to acquire resistantence to antibiotics. Nowadays, methicillin-resistant S. aureus (MRSA) are responsabilized for nosocomial infections and many studies are done because MRSA are spread to extra hospitalar enrivonment and frequentely isolated from domestic animals including pigs. The aim of this study was to determine the presence o S. aureus at swine farms and identify the mecA, icaA and icaD genes and the resistant proflife to antibiotics. Overal, 458 swabs were taked from five pigeris and two slautherhouses. All the samples were placed on Braid - Parker and blood agar follow by biochemical analyses. The suspect colonies were submitted to PCR to confirm the S. aureus species, by the detection of the coa gene, mecA to avaible meticillin-resistant as son to the virulence gens icaA and icaD that can determine slime production. Antibiogram were done to evaluate the response to 11 antibiotics. All pigeris and slautherhouse were positive and 81 (79%) samples were S. aureus positive including four isolates from pigs employeers. The mecA gene was not detected. The icaD gene was most frequent and 41% were positive to both genes. The antibiogram show a lot of samples penicillin and tetraciclin resistant. Most of the samples were multirestant.
Antibiotic resistant profile of Staphylococcus aureus isolated from pigs farms and slautherhouses
Keywords: Antibiogram; Mrsa; Pig; Resistant; Slime; Staphylococcus